Etiologies of neonatal seizures in infants of different gestational age - A. N. Zavadenko; M. I. Medvedev; M. G. Degtyareva; S. O. Rogatkin; N. N. Zavadenko (Эпилепсия и пароксизмальные состояния)
Aim: To determine main etiologies and clinical features of neonatal seizures (NS) in groups of newborns of different gestational age (GA).Materials and Methods. Main etiologies of NS were evaluated in 165 newborns divided into four groups: I – 84 early preterm newborns with GA of 28 weeks or less, II – 52 newborns with 29-32 weeks GA, III – 12 newborns with 33-36 weeks GA, and IV – 17 term infants with GA between 37 and 41 wks.Results. In the above 165 infants, the following causes of NS were found: perinatal hypoxia-ischemia – 72.1% of cases, grade III-IV intracranial hemorrhage – 6.1%, congenital infections in 9.7%, CNS infections (bacterial meningitis and viral meningoencephalitis) – 9.7%, сerebral dysgenesis – 1.2%, and inborn errors of metabolism and neurodegenerative diseases accounted for 1.2%. Intracranial hemorrhage (grade III-IV) was detected in newborns with GA less than 32 wks only. The etiological role of CNS infections was higher in term newborns (23.5%) than in the other groups.Conclusion. In examining newborns with NS, genetic mechanisms should be taken into consideration, especially when no indications of early brain damage are apparent. This approach is important today as targeted therapies of gene-associated epileptic syndromes are becoming feasible. In the present article, the use of levetiracetam in infants with NS and early onset epilepsy is discussed.